Ambrosia trifida L. - Giant ragweed - Božić, Dragana; Vrbničanin, Sava (Acta herbologica, 2021)
Ambrosia trifida L. (AMBTR, fam. Asteraceae/Compositae) is native to North America and in Europe was introduced at the end of the 19th century accidentally with contaminated animal feed and seeds for planting. Today A. trifida present in meny countries in Europe in ruderal and agricultural habitats (France, Italy, Germany, Russia, Spain, Romania, Slovakia, Czech Republic, Poland, Serbia, Bulgaria etc.). The first time gaint ragweed detected 1981 in Serbia (site Čoka) but in the following period it disappeared from this site, and again was recorded 2006 in other site of country (central Bačka). Currently in Serbia it has the status of alian naturalized weed species. This is a summer annual plant can grow up to 6 m height and exhibits a high degree of morphological and reproductive plasticity in response to encroachment by neighboring plants. It present in disturbed habitats such as agriculture fields it plays the role of the dominant species throughout the entire growlng season. In most cases, leaves are opposite and always simple and generally have 3 distinct lobes, but can have as many as 5. It is a diploid species (2n = 24), meso-hygrophilic, preferring wet habitate and can tolerate a wide variety of soil types. Also this is monoecious plant where male and female flowers are separated on the same individual. Also A. trifida can hybridise with A. artemisiifolia (A. x helenae Rouleau, with 2n= 27 and 2n= 33) but this hybride is described as sterile. Compared to other summer annual species, A. trifida is among the first to emerge in early spring at optimal temperature from 10-24°C. Under optimal environmental conditions, giant ragweed produces around 1,800 (max 5,100) seeds plant-1. Flowering and bears fruit from July to September (October). Also, pollen of this species has allergenic potential. In USA and Canada giant ragweed populations developed resistant to herbicide acetolactate synthase inhibitors and glyphosate. Giant ragweed can be problematic weeds in row crops (corn, soybean, sunflower, sugerbeet) and vegetables. For A. trifida control should prevent spreading and existing populations should be controlled by integrated weed management practices. Furthermore, A. trifida has a relatively low fecundity, a transient soil seed-bank and a high percentage of non-viable or low-survivorship seeds, features which may have constrained its establishment and spread in the current environmental conditions in Serbia.